Demography and development: historical experience and current problems of the Kabardino-Balkarian Republic - Aslan Kh. Borov (Кавказология, 2024)
The demographic characteristics of society act at any given moment as factors determining the possibilities and limitations of socio-economic development, but over long historical stages, they themselves change under the influence of socio-economic changes. This relationship should be considered when setting goals and objectives for both economic and demographic policies at the national and regional levels. This paper provides a review of the leading trends and results of the economic and socio-demographic evolution of Kabardino-Balkaria during the Soviet era and the main features of the current demographic situation in the context of the region’s transition to an innovative path of socio-economic development. The socio-economic modernization of the Soviet period was accompanied by demographic modernization. The population of Kabardino-Balkaria grew rapidly and acquired a new sociocultural appearance, becoming more diverse in ethnic composition, urban in settlement structure and way of life. By the end of the Soviet era, the demographic transition was completed, the level of education of the population of the republic was comparable to all-Russian parameters, its socio-professional structure acquired a diversified and generally modern character. However, the transition from the Soviet to the post-Soviet social and state system was accompanied not just by a deep economic recession, but by the phenomena of structural deindustrialization and demodernization. A reflection of these socio-economic conditions is the ambivalence of the demographic situation – a significant slowdown in natural growth, the aging of the population, a shift in the age distribution of marriage and birth rate towards older ages, a change in the vector of migration processes from inflow to outflow, a decrease in the share of the urban population, a reduction in industrial employment, a decline in the Russian population, reaching a plateau in dynamics and a deterioration in comparative indicators of the level of education. Meanwhile, qualitatively new tasks have appeared on the agenda, placing increased demands on the quality of human potential of modern development.